Prediction of Biological Motion Perception Performance from Intrinsic Brain Network Regional Efficiency - Wang, Zengjian; Zhang, Delong; Liang, Bishan; Chang, Song; Pan, Jinghua; Huang, Ruiwang; Liu, Ming (Frontiers in Human Neuroscience, 2016)
Biological motion perception (BMP) is a vivid perception of the moving form of a human figure from a few light points on the joints of the body. BMP is commonplace and important, but there is great inter-individual variability in this ability. This study used multiple regression model analysis to explore the association between the BMP performance and intrinsic brain activity, in order to investigate the neural substrates underlying inter-individual variability of BMP performance. The resting-state functional magnetic resonance imaging (rs-fMRI) and BMP performance data were collected from 24 healthy participants. For each participant, the intrinsic brain network was constructed, and a graph-based network efficiency metric was measured. Then, a multiple linear regression model was used to explore the association between network regional efficiency and BMP performance. We found that the local and global network efficiency of many regions was significantly correlated with the BMP performance. Further analysis showed that the local efficiency rather than global efficiency could be used to explain most of the BMP inter-individual variability, and the regions involved were predominately located at the Default Mode Network (DMN). Additionally, the discrimination analysis showed that the local efficiency over regions including thalamus could be used to classify BMP performance across participants. Notably, the association pattern between the network nodal efficiency and the BMP was different from the association pattern that of the static directional/gender information perception. Overall, these findings showed that intrinsic brain network efficiency may be considered as a neural factor that explains BMP inter-individual variability. Keywords: Biological motion; Resting-state network; Network efficiency; Multiple linear regression model; Brain-behavior analysis